Voting behavior under outside pressure: promoting true majorities with sequential voting? - Friedel Bolle; Philipp E. Otto (Social Choice and Welfare, 2021)
When including outside pressure on voters as individual costs, sequential voting (as in roll call votes) is theoretically preferable to simultaneous voting (as in recorded ballots). Under complete information, sequential voting has a unique subgame perfect equilibrium with a simple equilibrium strategy guaranteeing true majority results. Simultaneous voting suffers from a plethora of equilibria, often contradicting true majorities. Experimental results, however, show severe deviations from the equilibrium strategy in sequential voting with not significantly more true majority results than in simultaneous voting. Social considerations under sequential voting—based on emotional reactions toward the behaviors of the previous players—seem to distort subgame perfect equilibria.
Keywords: 330; Economic Theory/Quantitative Economics/Mathematical Methods; Public Finance; International Political Economy; Game Theory; Economics; Social and Behav. Sciences; Social Policy